2020
DOI: 10.1002/nafm.10412
|View full text |Cite
|
Sign up to set email alerts
|

Natural Recolonization by Pacific Lampreys in a Southern California Coastal Drainage: Implications for Their Biology and Conservation

Abstract: The historical range of anadromous Pacific LampreyEntosphenus tridentatus includes coastal drainages from Alaska south to northern Baja California. However, there has been a widespread loss of distribution inland due to the construction of dams that form impassable barriers as well as a loss of Pacific Lampreys from some historically occupied drainages in the south. These losses have prompted the consideration of suitable approaches to reestablishing Pacific Lamprey populations through either active interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…Endangered Species Act, and other biota. Although data on steelhead response to dam removal on the Carmel River are not yet published, Pacific lamprey ( Entosphenus tridentatus ) have successfully recolonized the Carmel River after dam removal and are spawning there (Reid & Goodman, 2020), indicating some ecosystem benefit. Our grain‐size analyses (Figure 9) show that by 2021, 6 years after dam removal, all reaches had average bed‐material size within the 5–75 mm range necessary for salmonid spawning (Kondolf & Wolman, 1993) and with less than 10% sand, consistent with appropriate salmonid spawning habitat.…”
Section: Discussionmentioning
confidence: 99%
“…Endangered Species Act, and other biota. Although data on steelhead response to dam removal on the Carmel River are not yet published, Pacific lamprey ( Entosphenus tridentatus ) have successfully recolonized the Carmel River after dam removal and are spawning there (Reid & Goodman, 2020), indicating some ecosystem benefit. Our grain‐size analyses (Figure 9) show that by 2021, 6 years after dam removal, all reaches had average bed‐material size within the 5–75 mm range necessary for salmonid spawning (Kondolf & Wolman, 1993) and with less than 10% sand, consistent with appropriate salmonid spawning habitat.…”
Section: Discussionmentioning
confidence: 99%
“…When habitat becomes accessible after dam removal or habitat improvements, it is useful to assess the relative merits of taking a passive approach to lamprey recolonization (relying only on volitional migrants) versus actively translocating lamprey to repopulate the newly available habitat (Reid and Goodman 2020). Due to the modest numbers of adults translocated in our study and the limited years available to monitor any translocation production, we could not fully assess the relative merits of these alternative approaches.…”
Section: Discussionmentioning
confidence: 99%
“…In smaller coastal systems, the species may need just an opportunity to access appropriate habitat to naturally re‐establish because these areas have fewer passage impediments and greater proximity to oceanic sources of Pacific Lamprey spawners. For small coastal rivers with dams that prevent passage of Pacific Lamprey, dam removal could be the only requisite for restoration of robust and self‐sustaining Pacific Lamprey abundance via natural recolonization (Reid and Goodman 2020; Moser et al., in press).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Spawning migration towards freshwater, however, is not philopatric regarding spawning locations; contrary to other anadromous fishes, sea lampreys do not return to the natal rivers to spawn (Almada et al, 2008; Bergstedt & Seelye, 1995; Spice, Goodman, Reid, & Docker, 2012). Instead, it has been suggested that sea lampreys are steered by a migratory pheromone released by stream-resident larvae (Sorensen et al, 2005; Vrieze, Bergstedt, & Sorensen, 2011), although natural recolonization of freshwater locations without ammocoete presence has been recently noted (Reid & Goodman, 2020). Less understood is how selection acts across the sea lamprey life cycle, despite its numerous life history events (such as the transition to parasitism linked to adulthood, onset of anadromous and catadromous migrations) providing substantial opportunities for selection to act.…”
Section: Introductionmentioning
confidence: 99%